Politics and historical imprisonment, 1930–2010 - Amidon, Ethan (Journal of crime and justice, 2018)
Theorists have argued that the increasing reliance on imprisonment in the late twentieth and the early twenty-first centuries is associated with a number of important social and political developments that began in the 1960s and 1970s. Despite the emphasis that has been placed on these historically contingent developments, scholars have yet to empirically examine whether the predictive power of recent political variables is restricted to the use of imprisonment in the late twentieth century. The current study addresses this gap in the literature by examining whether four political perspectives are able to account for the use of incarceration at the state level from 1930 to 2010. This study also examines whether the movement from the early to the late twentieth century changed the nature of the relationship between political considerations and jurisdictional reliance on imprisonment. The results indicate that the political party affiliation of elected officials, the public’s commitment to religious fundamentalist sentiment, and the size of African-American populations are significant predictors of imprisonment across the twentieth and early twenty-first centuries.